Influence of epidemic COVID–19 on business strategy, information technology and supply chain agility to firm performance in medical device industry - Maemunah, Siti; Cuaca, Herry (Linguistics and Culture Review, 2021)
Research related to the impact of the COVID-19 pandemic on business strategy, information technology, and supply chain agility on firm performance in the medical device industry in Indonesia. The analysis used is the Structural Equation Model (SEM) with the AMOS program. The study had 171 respondents. The findings in this study are that business strategy, information technology, and supply chain agility have a positive and significant influence on firm performance during the COVID-19 pandemic. The practical implication is that business strategies and information technology save companies and society by involving supply chain agility in securing the supply of medical devices in Indonesia. It is recommended that further research consider not only focusing on medical devices but also larger or different areas to elicit different responses. The practical implications provide direction for adopting business strategies, information technology, supply chain agility in improving firm performance.